Cubic mesoporous Pd–WO3 loaded graphitic carbon nitride (g-CN) nanohybrids: highly sensitive and temperature dependent VOC sensors. Issue 23 (23rd May 2018) - Malik, Ritu; Tomer, Vijay K.; Dankwort, Torben; Mishra, Yogendra Kumar; Kienle, Lorenz
Abstract : The Pd–WO3 /m-CN sensor, exhibits enhanced response/recovery times to 25 ppm VOCs and formaldehyde under fluctuating humidity conditions. Abstract : The urgent need for real-time monitoring of toxic/hazardous gases in the immediate indoor environment has attracted much attention owing to the recent advancements in the development of ultra-efficient gas sensors with increased accuracy and portability at around room temperature. In this work, we report on a high performance volatile organic compound (VOC) sensor using a Pd–WO3 loaded ordered mesoporous graphitic carbon nitride (g-CN)-based nanohybrid prepared via a nanocasting strategy on a hard 3D porous silica (KIT-6) template. The nanocasted Pd–WO3 /g-CN sensor exhibits highly selective temperature dependent trace detection of important VOCs (formaldehyde, toluene, acetone and ethanol), which are commonly present in the indoor climate. The 3D cubic ordered mesoporous structure of the 2D layered g-CN in the hybrid nanodevice is very advantageous towards improving its sensing response with enhanced linearity, swift response/recovery time, selectivity, reversibility, stability with respect to various VOCs (at their respective optimum temperature) and reusability. The proposed functional hybrid nanomaterial-based sensing strategy offers an effective design for highly sensitive and efficient VOC detection devices, which can operate well at low temperatures also.